A NEED ANALYSIS OF ESP FOR PUBLIC HEALTH STUDENTS - Risa Arroyyani; Dewi Nur Widiyati; Maryani Maryani (Universitas PGRI Palembang, 2022)
This study is aimed at finding out the students' needs in learning English, particularly English for Public Health as part of ESP regarding four language skills and some language areas.This study was a qualitative descriptive study with 150 students of Public Health Department as the subjects. The data were collected by using a questionnaire. A semi-structured questionnaire was distributed to the participants to gather information related to the students' needs and wants.The study analyzes the data from the closed questions by using simple statistics and the open question by using interpretations.The results showed that the students were confidentin their Reading skillsbut not in Grammar, they also perceived that writing skill is the most important skill to learn. For each sub-skill, the students perceived that the most important skills to learn are including understanding vocabulary from the context (reading), writing correct sentences (writing), pronouncing words correctly (speaking), and listening to English media (listening). Related to their wants, the students not only learn English to support their academic field, but also to prepare after graduation.